Musculoskeletal health in children and adolescents - Faienza, Maria Felicia; Urbano, Flavia; Chiarito, Mariangela; Lassandro, Giuseppe; Giordano, Paola (Frontiers in Pediatrics, 2023)
The purpose of this narrative review was to investigate the key determinants of musculoskeletal health in childhood and adolescence, with particular attention to the role of physical activity. First, we examined the importance of bone modeling and remodeling in maintaining the bone health and the integrity and mechanical characteristic of the skeleton. In addition, we reported the evidence on an appropriate calcium and vitamin D intake, as well as local load variation in achieving proper peak bone mass. Proteomic and transcriptomic studies identified the skeletal muscle "secretoma", consisting of several myokines involved in endocrine and paracrine functions.Among these, we explored the role of irisin, a myokine involved in the muscle-bone crosstalk, and in the regulation of metabolic pathways. It is known that physical activity during growing positively impacts on skeleton and can protect by bone loss in adulthood. However, there are still concerns about the optimal interval duration and exercise intensity, particularly at the pubertal growth spurt which represents a window of opportunity to increase skeletal strength. We reported data from clinical trials performed in the last 5 years analyzing the impact of the type and timing of physical activity during childhood on skeletal development. Finally, we reported recent data on the significance of physical activity in some rare diseases.